EFFECT OF INITIAL IRRIGATION TIME AND WEED MANAGEMENT ON GROWTH AND YIELD OF CHICKPEA - SAHAJA DEVA, (The Journal of Research ANGRAU, 2023)
Studies were carried out during Rabi (winter) season for two years in chick pea and the results revealed that thehighest crop stand was found in irrigation after sowing (pooled mean of 16.91). Among weed management practices, crop standwas the maximum in control (pooled mean of 17.71). Hand weeding twice was superior in obtaining maximum plant height, numberof nodules, nodule dry weight, seed yield (pooled mean of 17.94 q ha-1), haulm yield (pooled mean of 19.33 q ha-1), harvest index(pooled mean of 48.07%), agronomic efficiency (pooled mean of 17.94), production efficiency (pooled mean of 15.87 kg ha-1day-1) and lowest weed density. Among herbicides, pre-emergence application of oxyfluorfen 0.3 kg ha-1 was superior inproducing maximum plant height, nodule number, nodule dry weight, seed yield (pooled mean of 15.82 q ha-1), haulm yield (pooledmean of 17.34 q ha-1), agronomic efficiency (pooled mean of 15.82), production efficiency (pooled mean of 14.00 kg ha-1 day-1) andlowest weed density.